2020
DOI: 10.3389/fimmu.2020.01643
|View full text |Cite
|
Sign up to set email alerts
|

Properdin Pattern Recognition on Proximal Tubular Cells Is Heparan Sulfate/Syndecan-1 but Not C3b Dependent and Can Be Blocked by Tick Protein Salp20

Abstract: Introduction: Proteinuria contributes to progression of renal damage, partly by complement activation on proximal tubular epithelial cells. By pattern recognition, properdin has shown to bind to heparan sulfate proteoglycans on tubular epithelium and can initiate the alternative complement pathway (AP). Properdin however, also binds to C3b(Bb) and properdin binding to tubular cells might be influenced by the presence of C3b(Bb) on tubular cells and/or by variability in properdin proteins in vitro. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Binding of properdin to viable cells has also been demonstrated for renal proximal tubular epithelial cells, where heparan sulfate was identified as a ligand to which properdin binds [ 16 , 17 ]. Therefore, we compared different polysaccharides to determine their inhibitory effect on the binding of properdin to different viable and dead cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Binding of properdin to viable cells has also been demonstrated for renal proximal tubular epithelial cells, where heparan sulfate was identified as a ligand to which properdin binds [ 16 , 17 ]. Therefore, we compared different polysaccharides to determine their inhibitory effect on the binding of properdin to different viable and dead cells.…”
Section: Resultsmentioning
confidence: 99%
“…Properdin is able to bind to proximal tubular epithelial cells and it has been shown that heparan sulfates are involved in this interaction [ 12 , 16 , 17 ]. We also investigated the properdin binding to viable DCs and macrophages and observed a properdin binding to both pro‐ and anti‐inflammatory macrophages (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, consumption of complement proteins in the glomeruli, such as in patients with glomerulonephritis, reduces the concentration of complement proteins entering the tubulointerstitium 29–31 . Experiments have also suggested that properdin can bind to tubular epithelial cells, potentially initiating AP activation on the surface of this specific kidney cell type 32 . Properdin can form non‐physiologic multimers during handling, however, so experiments with purified properdin need to be interpreted cautiously.…”
Section: Cell Types and Surfaces In The Kidneymentioning
confidence: 99%